2006
DOI: 10.1007/s00203-006-0133-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Vibrio cholerae vexAB and vexCD efflux systems

Abstract: Vibrio cholerae is an important human pathogen that causes the diarrheal disease cholera. Colonization of the human host is dependent upon coordinated expression of several virulence factors in response to as yet unknown environmental cues. Bile acids have been implicated in the in vitro regulation of several V. cholerae genes, including those involved in motility, chemotaxis, outer membrane protein production, and virulence factor production. Bile is toxic to bacteria and colonization of the intestinal tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 53 publications
4
97
1
2
Order By: Relevance
“…The major substrates for the VexCD were cholates. These properties are essentially consistent with those of VexAB and VexCD in V. cholerae O1 (5). By comparing the deduced amino acid sequences, we found that the sequence identities of VexAB and VexCD between V. cholerae NCTC4716 (non-O1) and V. cholerae N16961 (O1) were 98% and 97%, respectively.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The major substrates for the VexCD were cholates. These properties are essentially consistent with those of VexAB and VexCD in V. cholerae O1 (5). By comparing the deduced amino acid sequences, we found that the sequence identities of VexAB and VexCD between V. cholerae NCTC4716 (non-O1) and V. cholerae N16961 (O1) were 98% and 97%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…We have so far characterized all of the six efflux transporters categorized in the MATE family from V. cholerae non-O1, NCTC4716 (2,18,19). Several drug efflux transporters belonging to other families have been reported in V. cholerae (O1, non-O1, and non-O139) (5,9,20).…”
mentioning
confidence: 99%
“…Namely, VmeAB could be involved in the escape from the instantaneous bactericidal effect of deoxycholate, and efflux transporters other than VmeAB might be involved in the growth in the presence of deoxycholate. In fact, expression of vexAB and vexCD, which encode RND-type efflux transporters in V. cholerae, has been shown to be induced by bile salts (Bina et al, 2006). Our results suggest that other multidrug transporter(s) which is (are) able to extrude deoxycholate is (are) present in V. parahaemolyticus.…”
Section: Discussionmentioning
confidence: 65%
“…In fact, two RND-type efflux transporters (VexAB and VexCD) in V. cholerae have been characterized (Bina et al, 2006). VmeAB shared high sequence similarity with AcrAB and MexAB, but to a lesser extent with VexAB and VexCD.…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotide PCR primers used for cloning are listed in Table 1. Deletion of vpsR (VC0665) in strain JB58 was constructed by homologous recombination using the allelic exchange plasmid pWM91 as previously described (Bina et al, 2006(Bina et al, , 2008. Briefly, 1 kb regions flanking vpsR were amplified by PCR using vpsR-F1/R2 and vpsR-F2/R1 primer pairs.…”
Section: Methodsmentioning
confidence: 99%